THE ROLE OF GOVERNANCE IN MODERATING CREDIT RISK AND CAPITAL ADEQUACY ON FINANCIAL PERFORMANCE IN INDONESIAN BANKS - Ega Monika Pili; Irfan Putra Fadrianto; Farah Margaretha Leon (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study seeks to contribute to the existing corporate governance literature by examining its role as a moderator on the relationship between credit risk (CR), represented with loans to total assets (LTA) and non-performing loans (NPLs), as well as capital adequacy ratio (CAR), on financial performance (FP) of banks listed in the Indonesia Stock Exchange (IDX). This study uses quantitative data collected from the annual reports of 45 banks listed on the IDX, utilizing panel data regression analysis techniques of total 180 firm-year observations within the 2020-2023 period, with fixed and random effect model to examine the hypotheses. The study’s findings demonstrated differing results between the variables, in which both LTA and CAR have a significant positive influence on return on equity (ROE), whereas it has inverse effects on Tobin's Q. Moreover, the regression results showed that corporate governance (CG) moderated the relationship between LTA and banks FP, as it weakens LTA effect on ROE but strengthens it on Tobin's Q. The study provides insights for bank managers and authorities alike in managing the proportion of LTA and the CAR while determine the optimal board size to stabilize banks performance better, as well as for investors to consider the importance of CR & CAR, as well as quality of governance in making investment decisions.